Utility of intravoxel incoherent motion magnetic resonance imaging and arterial spin labeling for recurrent glioma after bevacizumab treatment. (November 2018) - Miyoshi, Fuminori; Shinohara, Yuki; Kambe, Atsushi; Kuya, Keita; Murakami, Atsushi; Kurosaki, Masamichi; Ogawa, Toshihide
Background: Detecting recurrence of glioma on magnetic resonance imaging (MRI) is getting more and more important, especially after administration of new anti-tumor agent. However, it is still hard to identify. Purpose: To examine the utility of intravoxel incoherent motion (IVIM) MRI and arterial spin labeling-cerebral blood flow (ASL-CBF) for recurrent glioma after initiation of bevacizumab (BEV) treatment. Material and Methods: Thirteen patients (7 men, 6 women; age range = 41–82 years) with glioma (high grade, n = 11; low grade, n = 2) were enrolled in the study. IVIM parameters including apparent diffusion coefficient (ADC), true diffusion coefficient (D), and perfusion fraction (f) were obtained with 14 different b-values. We identified tumor progression during BEV therapy by MRI monitoring consisting of diffusion-weighted imaging (DWI), fluid-attenuated inversion recovery (FLAIR) imaging, and contrast-enhanced T1-weighted (CE-T1W) imaging by measuring tumor area. We also measured each parameter of IVIM and ASL-CBF, and calculated relative ADC (rADC), relative D (rD), relative f (rf), and relative CBF (rCBF) by obtaining the ratio between each area and the contralateral cerebral white matter. We calculated the rate of change (Δ) by subtracting values from those from the preceding MRI study, and obtained Spearman's rank correlation coefficient (rs). Results: Tumor progression was identified in nine patients (high grade, n = 7; low grade, n = 2). Negative correlations were identified between ΔrD and ΔDWI area (rs = –0.583), and between ΔrD and ΔCE-T1W imaging area (rs = –0.605). Conclusion: Tumor progression after BEV treatment can be identified by decreasing rD.